Finding elevation : fear and courage on the world's most dangerous mountain - Thompson, Lisa (Mountaineer) (Girl Friday Books, 2023)
"Near the death zone on K2, the world's second-highest mountain, Lisa Thompson searched for the strength to continue climbing. Her choices were clear: give in to her doubts and descend or push past her own limits and continue up the mountain's steep face. Defiance had provoked Thompson to enter the male-dominated world of high-altitude mountaineering, but defiance could only take her so far. After a harrowing battle with cancer, Lisa realized she needed to understand what motivated her to take greater and greater risks in the mountains. Finding Elevation chronicles Thompson's path from novice climber to world-class mountaineer, as she becomes the second American woman to summit K2, which is considered by many to be the most dangerous mountain in the world. More than a climbing memoir, Finding Elevation is a deeply personal examination of motivation and the human spirit. It is a story of what can happen when we finally stop letting others define our limits and instead trust that we are capable of more. In this inspiring book, Thompson reaches beyond the mountain to tell a story of heartbreak, resilience, and the discovery that we are responsible for defining our own boundaries, finding our own happiness, and facing our fears head-on"--